On line optimal control of variable speed compressor motor drive system using neural control model - Abdul Halim Mohamed Yatim, 1959-; Wahyu Mulyo Utomo; Malaysia Power and Energy Conference (2004 : Shah Alam, Selangor) (Skudai : Universiti Teknologi Malaysia, 2004)
15